Subcapsular hematoma of the liver of traumatic origin in children - Murguia de Roso, Elida (2020)
A case of superficial subcapsular hematoma of the liver in an 8 year oldchild, of traumatic causation, is reported upon. The tumor mass and the acute anemia set in progressively after the accident. A survert is carried out of similar cases reported in Uruguay and of the different varietes of sub-capsular injury of the liver, its degree of severity and the best approachto the problem.